PENGEMBANGAN MEDIA KOMIK DIGITAL BERMUATAN KUIS INTERAKTIF UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPAS SD - Luh Eka Wahyuni; I Ketut Gading; I Gede Margunayasa (STKIP Subang, 2026)
This study was conducted based on the low level of students’ learning activity and learning outcomes in science (IPAS) subjects at elementary school. The purpose of this research was to develop a digital comic media integrated with interactive quizzes to improve students’ learning activity and learning outcomes. This study employed a Research and Development (R&D) method using a development model consisting of several stages, including analysis, design, development, implementation, and evaluation. The subjects of this study were fifth-grade elementary school students, divided into experimental and control groups. Data were collected through tests (pretest and posttest), and questionnaires. The data were analyzed using descriptive and inferential statistical techniques, including N-Gain analysis and hypothesis testing using MANOVA. The results showed that the developed digital comic media was valid, practical, and effective in improving students’ learning activity and learning outcomes. This is evidenced by the increase in students’ posttest scores compared to pretest scores, as well as higher learning activity in the experimental group compared to the control group. Furthermore, the MANOVA test results showed a significant effect with a significance value of 0.000 < 0.05, with Pillai’s Trace = 0.807 and F = 77.257, indicating a simultaneous significant effect on students’ learning activity and learning outcomes. The univariate test also showed significant results for learning activity (F = 4.953; Sig. = 0.032) and learning outcomes (F = 155.817; Sig. = 0.000). Therefore, the digital comic media integrated with interactive quizzes can be used as an innovative learning medium to support effective science learning in elementary schools.